Recent advances in carbon-supported noble-metal electrocatalysts for hydrogen evolution reaction: syntheses, structures, and properties - Liu, Yuhang (2022)
The electrochemical hydrogen evolution reaction (HER) that converts renewable electricity into storable hydrogen, a sustainable and clean energy carrier, provides a promising method to mitigate the energy crisis and environmental pollution. In general, noble-metal-based nanomaterials (including Pt, Rh, Ru, Ir, etc.) have drawn tremendous research attention in the context of the HER because of their nearly optimal bindings to hydrogen, robust stability and tunable physical/chemical properties. Particularly, carbon as a substrate not only offers a stabilizing and conductive matrix, but also impacts the electronic structure of the supported metal by interfacial interaction, necessitating a detailed understanding. To speed up the sluggish kinetics of the HER, the design and construction of efficient electrocatalysts is of crucial importance. Herein, a comprehensive review of the recent advances in carbon-supported noble-metal electrocatalysts is presented, focusing on their synthetic strategies, structural analyses, and applications in HER electrocatalysis. Specifically, the correlation between the electronic structure and activity is discussed. Furthermore, a perspective is offered highlighting the challenges and opportunities for development of highly efficient HER electrocatalysts, with the aim for widespread utilization of practical water electrolyzers toward green hydrogen production.